The Thinking Organization: Dynamics of Organizational Social CognitionThe Thinking Organization: Dynamics of Organizational Social Cognition, by SimsHenry P.Jr., Gioia Dennis A. and Associates. San Francisco: Jossey-Bass, 1986, 375 pp., $28.95, cloth. - Meindl, James R. (Academy of Management Review, 1987)
The article reviews the book ?The Thinking Organization: Dynamics of Organizational Social Cognition,? by Henry P. Simms, Jr., Dennis A. Gioia, and associates.